2018
DOI: 10.3390/nu10050619
|View full text |Cite
|
Sign up to set email alerts
|

Buckwheat and CVD Risk Markers: A Systematic Review and Meta-Analysis

Abstract: The effects of buckwheat intake on cardiovascular diseases (CVDs) have not been systematically investigated. The aim of the present study was to comprehensively summarize studies in humans and animals, evaluating the impact of buckwheat consumption on CVD risk markers and to conduct a meta-analysis of relevant data. Thirteen randomized, controlled human studies, two cross-sectional human studies and twenty-one animal studies were identified. Using random-effects models, the weighted mean difference of post-int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 104 publications
(108 reference statements)
0
16
1
1
Order By: Relevance
“…In a meta- , compared with the control group. However, only triglycerides and total cholesterol showed slight differences in animals, with high heterogeneity [40]. On the other hand, another trial on quinoa suggested that quinoa consumption can regulate glucose response, with only minimal effects on other CVD risk biomarkers [41].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta- , compared with the control group. However, only triglycerides and total cholesterol showed slight differences in animals, with high heterogeneity [40]. On the other hand, another trial on quinoa suggested that quinoa consumption can regulate glucose response, with only minimal effects on other CVD risk biomarkers [41].…”
Section: Discussionmentioning
confidence: 99%
“…Rutin has attracted much attention mainly because of its many health benefits observed in vitro and in vivo: anti-inflammatory, antidiabetic, hypocholesterolemic, antiatherogenic, antiatherosclerotic, and anticancer ones [4,12,36,[50][51][52][53] and its activity are related to antioxidant capacity [54]. Furthermore, rutin may be effective in preventing the toxic effects of methotrexate on the kidneys [55].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In fact, the epidemiological studies conducted in southwest China (He et al, 1995) and inner Mongolia ( Zhang et al, 2007) revealed that low density lipoproteins (LDL) and serum total cholesterol were considerably low in participants consuming BW. BW-based dietary interventions are known to significantly reduce the total cholesterol in rats compared to controls, providing valuable protection against coronary heart diseases (Li et al, 2018). Owing to its remarkable slow digestibility, a strong hypocholesterolemic effect of BW protein was observed in the blood plasma of rats fed with cholesterol-enriched diets (Kayashita et al, 1997).…”
Section: Cardio-protective Propertiesmentioning
confidence: 99%